PENERAPAN VIDEO PEMBELAJARAN BERBASIS STEM TERHADAP HASIL BELAJAR KOGNITIF SISWA SMK DI SMKN 1 DLANGGU - Jasmine Syahda Sasmita; Nugrahani Astuti; Febriani Lukitasari; Rendra Lebdoyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine of implementing STEM-based instructional videos on students’ cognitive learning outcomes at SMK Negeri 1 Dlanggu. This study employed a quantitative approach using a one-group pretest-posttest design. Data collection included observations, learning outcome tests (pretest and posttest), and student response questionnaires. Data were analyzed using descriptive and inferential statistical analysis. The results showed that: (1) the implementation of learning based on the observation of teacher activities reached 97.03% and student activities reached 98.44%, both categorized as very good; (2) students' cognitive learning outcomes improved, as indicated by the increase in the average pretest score from 70.88 to 88.24 in the posttest, with an N-Gain value of 0.58 (moderate category), and the Wilcoxon test showed a significance value of 0.000, indicating a significant effect; and (3) students' responses to the implementation of STEM-based learning videos reached 92.24%, categorized as very good